Modern Language Notes: tomo 63 (1948), tomo 64 (1949), tomo 65 (1950), tomo 66 (1951). - Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1956)
Se reseñó: Modern Language Notes: tomo 63 (1948), tomo 64 (1949), tomo 65 (1950), tomo 66 (1951).